ANALISIS IMPLEMENTASI SISTEM INFORMASI MANAJEMEN SDM ORANGEHRM, STUDI KASUS BAGIAN KEPEGAWAIAN STT NF - Rusmanto Rusmanto (Jurnal Informatika Terpadu, 2015)
Information technology is increasingly needed by various institutions, among others, to facilitate HR management (Human Resources). Low cost is one of the criteria for selecting an information system application for HR management. The use of open code office computer software applications that can be obtained at a low cost for the administration of employees or human resources does not meet that need because it is not systematic, so there are still some problems such as difficulty accessing information employees quickly and accurately. Research has been carried out to implement system applications OrangeHRM HR information with the case study method at the College of Technology Personnel Section Integrated Nurul Fikri or STT NF. OrangeHRM was chosen because it is an open-source license fee-free and, based on previous research, has been successfully implemented in the company. Analysis result this research shows that the use of the OrangeHRM application has met the basic needs of the system HR information in institutions similar to STT NF, including the available HR information system administration module, which easy to use personnel department, personal information management module, time attendance module and implementation of activities, leave module, employee recruitment module, performance module, and report module. For more efficiency according to institutional needs, this open code licensed OrangeHRM can be developed further without technological and legal barriers.